'Changing the System': Compensatory versus Transformative Social Entrepreneurship. Issue 1 (2nd January 2018) - Newey, Lance R.
ABSTRACT: 'Changing the system' has long been a part of definitions of social entrepreneurship (SE). This paper focuses on capitalism as a global socio-economic system and understanding the role of SE in relation to this system. A distinction between two types of SE activity is introduced: compensatory and transformative. Compensatory SE compensates for market failures within the global capitalist system. By contrast, transformative SE specifically seeks to change the system of global capitalism. Using the examples of the alter-globalization movement and transition towns, the paper advances a conceptualization of transformative SE which contrasts assumptions with compensatory SE. This distinction aids to make the field of SE more truly global, multidisciplinary, representative and emancipatory.